The gap in knowledge of clinical practice guidelines by mental health residents in Buenos Aires (Argentina) - Fabrissin, Javier (2014)
The aim of this pilot study was to evaluate if the residents of psychiatry and clinical psychology from the city of Buenos Aires knew any of the existing mental health Clinical Practice and Treatment Guidelines (CPTGs). We asked residents their opinion about CPTGs and, also, if they followed their recommendations in clinical practice. We asked 59 mental health residents (28 physicians and 29 psychologists) with different years of clinical training to fill a questionnaire to know their opinion about CPTGs and also if they follow the CPTG recommendations in their clinical practice. We found that 79.31% of residents did not know any CPTG. Eighty percent of the residents who did know any CPTG have a positive opinion about CPTGs. Finally, the American Psychiatric Association Guidelines were the most known CPTGs. The authors emphasize the need for a clinical guidelines diffusion policy in Buenos Aires city and particularly as a clinical and training resource for mental health residents.